Recent advances of bismuth based anode materials for sodium-ion batteries. (3rd July 2018) - Sun, Jianguo; Li, Minchan; Oh, Jin An Sam; Zeng, Kaiyang; Lu, Li
ABSTRACT: Recent advances in Na-ion battery have made it more attractive and promising for large-scale energy storage. Emerging of Na-ion battery technology is closely associated to recent achievements in discovery of many suitable active materials, special capability of Na ion transportation, and of course the merits of abundance raw Na sources and environmental friendliness. Among all types of anode materials, bismuth-based anode materials, with a comparable theoretical specific capacity, as new high efficient electrode materials have sprung up for Na-ion batteries. However, the low electrical conductivity and fast capacity fading are still the two key challenges limiting their potential application. Great efforts have been devoted to mitigate these challenges and remarkable progresses have been achieved. In this mini-review, recent advances in bismuth-based materials as anode materials for Na-ion batteries are comprehensively reviewed with providing insights for the potential challenges in the development of bismuth-based materials for electrochemical energy storage devices.